SYNERGIZING PROPHETIC VALUES AND PHYGITAL LEARNING: A HOLISTIC FRAMEWORK FOR CONSCIENCE DRIVEN ENTREPRENEURSHIP EDUCATION - Siti Atwano Pisriwati; Yuwono Hardi; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2026)
This research aims to explore the implementation of the entrepreneurship program at SMA Muhammadiyah Mlati. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation of